Tinjauan Strategis: Pengaruh Keunggulan Kompetitif dan Orientasi Pasar terhadap Kinerja Bisnis UMKM dalam Konteks Pasar yang Kompetitif - Didit Darmawan; Rahayu Mardikaningsih; Siti Nur Halizah; Arif Rachman Putra; Eli Retnowati; Misbachul Munir; Rafadi Khan Khayru; Eli Masnawati; Samsul Arifin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research aims to explore the influence of competitive advantage and market orientation on a company's business performance. The research method used in this research includes quantitative models. A sample consisting of 75 small business owners in Suranaya City representing their companies filled out the survey using predetermined measurements. Purposive sampling will be used for sampling requirements. The collected data was analyzed using various statistical techniques, including classical assumption testing, multiple linear regression, and hypothesis testing. The research results show that there is a significant positive relationship between competitive advantage and business performance. Companies that are able to develop competitive advantages in products, services, or costs tend to achieve better financial results than their competitors. Apart from that, market orientation also has a significant positive influence on business performance. Companies that focus more on understanding customers in depth and trying to meet their needs tend to have better business performance.